The Effect Of Market Value Added (Mva) And Inflation On Stock Prices (Study On Automotive And Component Sub-Sector Companies Listed On The Indonesia Stock Exchange 2018-2022) - Musaropah, Mida Hamidatul; Rahwana, Kusuma Agdhi; Yuniar, Evilia Sri (Jurnal Pusat Manajemen, 2025)
This study aims to determine the effect of Market Value Added (MVA) and Inflation on Stock Prices in automotive and component sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2022, both simultaneously and partially. This study uses quantitative research methods. The research sample was 10 automotive and component companies obtained by purposive sampling technique. The analytical tool used in this research is panel data regression using eviews 12. The results of this study can be concluded that Market Value Added (MVA) and Inflation simultaneously have a significant effect on stock prices. While partially Market Value Added (MVA) has a significant positive effect on stock prices and Inflation has a significant negative effect on stock prices.